2009
DOI: 10.17796/jcpd.34.2.u665328k4g467pg2
|View full text |Cite
|
Sign up to set email alerts
|

Dental Treatment under General Anesthesia in Healthy and Medically Compromised/Developmentally Disabled Children: A Comparative Study

Abstract: Aim: To compare the type, number of procedures and working time of dental treatment provided under dental general anesthesia (DGA) in healthy and medically compromised/developmentally disabled children(MCDD children). Design: This cross-sectional prospective study involved 80 children divided into two groups of 40 children each. Group 1 consisted of healthy and Group 2 consisted of MCDD children. Results:Healthy children needed more working time than MCDD children, the means being 161±7.9 and 84±5.7 minutes, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
2
15
1
4
Order By: Relevance
“…Comprehensive DGA has earlier been reported in many European countries [8,9,11,19-21], North America [7,22,23], the Middle East [24,25], Asia [26,27] and New Zealand [28]. Contradictory findings have recently been reported from Australia and England, where DGA is used primarily for extractions in both children and adults [29-31], although a move towards comprehensive DGA care has also been made in the United Kingdom since the publication of the Royal College of Surgeon’s guidelines for the use of GA in paediatric dentistry in 2008 [32].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive DGA has earlier been reported in many European countries [8,9,11,19-21], North America [7,22,23], the Middle East [24,25], Asia [26,27] and New Zealand [28]. Contradictory findings have recently been reported from Australia and England, where DGA is used primarily for extractions in both children and adults [29-31], although a move towards comprehensive DGA care has also been made in the United Kingdom since the publication of the Royal College of Surgeon’s guidelines for the use of GA in paediatric dentistry in 2008 [32].…”
Section: Discussionmentioning
confidence: 99%
“…When treating patients with special needs, dentists tend to reduce the risk of failure and simplify treatment; for instance, if a tooth has an inflamed pulp, the tooth would be extracted rather than have root canal followed by a restoration 10 . Loyola–Rodriguez et al 11 . found that the overall number of operative and endodontic procedures carried out on healthy children who were treated under GA was significantly higher than the number of operative procedures carried out on children who were medically compromised or developmentally disabled.…”
Section: Introductionmentioning
confidence: 99%
“…When treating patients under GA, practitioners often tend to be more radical in treatment decisions and carry out less complex procedures to avoid the need to repeat treatment if that treatment fails 5,6,8–11 . These factors are important both for patients with SD and DD.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that children with disabilities receive less restorative treatments than their healthy counteparts . Conversely, it has been reported that healthy patients need a longer duration of treatment and increased number of treatment procedures than SNP . A Greek study also reported that patients with disabilities might undergo more treatments than healthy patients .…”
Section: Discussionmentioning
confidence: 99%
“…26 Conversely, it has been reported that healthy patients need a longer duration of treatment and increased number of treatment procedures than SNP. 27,28 A Greek study also reported that patients with disabilities might undergo more treatments than healthy patients. 29 Dentists generally prefer less complex procedures for SNP than healthy patients to avoid complications or necessity for retreatment.…”
Section: Discussionmentioning
confidence: 99%